Therapeutic potential of curcumin in dermatological conditions: mechanisms, clinical evidence and safety considerations - Stadnicka, Olga; Popielarska, Kinga; Opalińska-Kubowicz , Marta; Musialska, Zuzanna; Protsenko, Yuliia; Kowalska, Marta; Barczewska, Magdalena; Marczak, Anna; Bieszczad, Dominika; Swojnóg, Marzena; Mazurek, Adam (Quality in Sport, 2026)
Curcumin, a pleiotropic polyphenol derived from Curcuma longa, has gained considerable interest as a potential adjuvant therapy in dermatology due to its anti-inflammatory, antioxidant, antimicrobial and immunomodulatory properties. Preclinical studies demonstrate that curcumin modulates key molecular pathways involved in skin disease, including NF-κB, JAK–STAT, MAPK and Nrf2 signalling, affecting keratinocytes, fibroblasts, melanocytes, sebocytes and cutaneous immune cells. These findings have led to an increasing number of clinical studies investigating oral and topical curcumin, novel formulations and photodynamic applications across various dermatological conditions, such as psoriasis, atopic dermatitis, acne, pigmentary disorders, chronic wounds and photoaging. Clinical evidence suggests potential benefit as an adjunct to standard therapy in psoriasis, inflammatory and pruritic dermatoses, limited vitiligo and selected wound-healing settings, while data for cosmetic and infectious indications remain preliminary. Overall, curcumin shows a favourable safety profile, with mostly mild gastrointestinal or local adverse effects, though emerging reports of hepatotoxicity and drug interactions warrant caution with high-dose or long-term systemic use. Its clinical translation is limited by poor bioavailability, heterogeneous formulations, small and methodologically weak trials and lack of outcome standardisation. This narrative review summarises current mechanistic and clinical evidence, highlights limitations and identifies priorities for future research to better define curcumin’s role in modern dermatology.